2013
DOI: 10.1093/bioinformatics/btt004
|View full text |Cite
|
Sign up to set email alerts
|

Decombinator: a tool for fast, efficient gene assignment in T-cell receptor sequences using a finite state machine

Abstract: The Decombinator package is implemented in Python (v2.6) and is freely available at https://github.com/uclinfectionimmunity/Decombinator along with full documentation and examples of typical usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 23 publications
0
87
0
1
Order By: Relevance
“…Differences between thymic and blood TCR sequence distributions allow us to infer subtle details of this "turning on" of the mouse immune system. by distinct recombination events, standard tools that assign a unique recombination scenario to each sequence (17)(18)(19)(20) give biased estimates that would limit our ability to detect the developmental changes that interest us here. In previous work (9, 10) we showed how to overcome this problem, using an approach that assigns probabilities to different ways of generating a sequence (see Materials and Methods for details).…”
Section: Significancementioning
confidence: 99%
“…Differences between thymic and blood TCR sequence distributions allow us to infer subtle details of this "turning on" of the mouse immune system. by distinct recombination events, standard tools that assign a unique recombination scenario to each sequence (17)(18)(19)(20) give biased estimates that would limit our ability to detect the developmental changes that interest us here. In previous work (9, 10) we showed how to overcome this problem, using an approach that assigns probabilities to different ways of generating a sequence (see Materials and Methods for details).…”
Section: Significancementioning
confidence: 99%
“…Biases were assumed as independent for this model. In Simulation B, biases were measured from the raw data, processed by Decombinator (Thomas et al 2013). The following generation parameters were learned from the nonfunctional (out of frame) CDR3 sequences: V and J genes usage, conditional probabilities for deletions in each gene, and junctional nucleotide probabilities, including junction length.…”
Section: Library Preparation For Tcr-seq and Data Preprocessingmentioning
confidence: 99%
“…The TRA/TRB data were analyzed by HighV-QEUST (Li et al 2013), Decombinator (Thomas et al 2013), IgBLAST (Ye et al 2013), and IMonitor, while the IGH/IGK/ IGL data were analyzed by HighV-QEUST, IgBLAST (Ye et al 2013), and IMonitor. Thomas et al (2013) reported that The data sets were obtained from the IMGT/LIGM-DB database (http://www.imgt.org/ligmdb/); searched by "Homo sapiens," "rearranged," "TRB," or "IGH"; and then the selected sequences were annotated manually (Annot. level=="manual") and annotated by V, D, J genes.…”
Section: Imonitor Outperforms Other Analytical Tools In Various Aspectsmentioning
confidence: 99%
“…Several tools and software have been developed for TCR and BCR sequence analysis, including iHMMune-align (Gaeta et al 2007), HighV-QEUST (Li et al 2013), IgBLAST (Ye et al 2013), Decombinator (Thomas et al 2013), and MiTCR (Bolotin et al 2013). These tools are equipped with useful functions, including V(D)J gene alignment, CDR3 sequence identification, and more, yet with obvious limitations.…”
mentioning
confidence: 99%